EVALUATION OF THE IMPACT OF CHANGES IN THE CITY ROAD SYSTEM ON TRAFFIC FLOWS - LEONARDO PASINI (TASK Quarterly, 2018)
This paper outlines a study carried out to answer the questions asked by an architect of the Siena Municipality Office during a conference at our Department on the management of traffic flows through the Siena North city road system. The purpose of the study was to ascertain if changes in the road system introduced and included in the new City Development Plan would resolve the current traffic congestion issues. In order to answer this question, we used the technology for the development of vehicle traffic system simulators which was introduced during our previous projects (TASK Quart. 14 (4) 405, 17 (3) 155, 20 (1) 9, 20 (3) 273).